2010
DOI: 10.5012/bkcs.2010.31.11.3093
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Charge Recombination Rate in Nanocrystalline SnO2by Thin Coatings of Divalent Oxides in Dye-Sensitized Solar Cells

Abstract: The core-shell SnO2@AO (A = Ni, Cu, Zn and Mg) films were prepared and the effects of coatings on photovoltaic properties were investigated. Studies on X-ray photoelectron spectroscopy, energy dispersive X-ray analysis and transmission electron microscopy showed the formation of divalent oxides on the surface of SnO2 nanoparticles. It was commonly observed that all the dye-sensitized core-shell films exhibited higher photovoltage than the bare SnO2 film. Transient photovoltage measurements confirmed that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Surface modification of the SnO 2 electrode with TiO 2 , ZnO, or Al 2 O 3 shell layers has been widely researched to overcome the poor dye uptake and reduce the electron recombination with the redox couple. , , We prepared SnO 2 /TiO 2 electrodes by TiCl 4 treatment followed by annealing at 500 °C, and we confirmed the effects of high TBP concentration. The photocurrent–voltage ( I – V ) characteristics of SnO 2 /TiO 2 electrodes employing E1 and E5 in the illumination and dark states are shown in Figure a and listed in Table .…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Surface modification of the SnO 2 electrode with TiO 2 , ZnO, or Al 2 O 3 shell layers has been widely researched to overcome the poor dye uptake and reduce the electron recombination with the redox couple. , , We prepared SnO 2 /TiO 2 electrodes by TiCl 4 treatment followed by annealing at 500 °C, and we confirmed the effects of high TBP concentration. The photocurrent–voltage ( I – V ) characteristics of SnO 2 /TiO 2 electrodes employing E1 and E5 in the illumination and dark states are shown in Figure a and listed in Table .…”
Section: Resultsmentioning
confidence: 62%
“…SnO 2 paste was prepared using nanocrystalline SnO 2 powder of 26 nm diameter as described in our previous paper . The prepared paste was deposited on FTO glasses (Pilkington, TEC-8, 8 Ω/square) by the doctor blade technique.…”
Section: Methodsmentioning
confidence: 99%
“…17 Moreover, adsorption of the conventional ruthenium-based dyes on the SnO 2 surface is rather restricted due to the similarity between the pH of the dye solution and the isoelectric point (IEP) of SnO 2 (pH = 4-5), which is one of the reasons for a low photocurrent. 18 To overcome such a low dye coverage, a modification of the SnO 2 surface has been proposed by the introduction of thin layers of metal oxides [19][20][21][22][23][24][25][26][27][28][29] with high IEPs such as TiO 2 (IEP at pH 4.7 for rutile and pH 6.2 for anatase), Cr 2 O 3 (IEP at pH 7.0), Y 2 O 3 (IEP at pH 9), ZnO (IEP at pH B 9), Al 2 O 3 (IEP at pH 9) and MgO (IEP at pH 12). Surface modification with high IEP oxides is anticipated to increase the amount of dye adsorption due to the fact that the carboxylate anions are electrostatically attracted to the positively charged oxide surface at pH below the IEP.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that amount of the adsorbed N719 dye was increased by about 75% after surface modification of SnO 2 with ZnO, which was responsible for the 67% increase in the photocurrent density. 22 Besides the role of increasing the dye adsorption amount, the thin oxide layer on the SnO 2 surface plays another important role in the protection of the electron back reaction from SnO 2 to the electrolyte, 27 which is in part responsible for the increased voltage after surface modification. Since the N719 dye cannot be fully covered on the bare SnO 2 , the empty site without the dye can act as a recombination center because it is directly exposed to the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…4 It was also shown that the metal oxide (Al 2 O 3 ,Cr 2 O 3 ,TiO 2 ,NiO, CuO, ZnO, MgO) passivation layer helps to increase the current density by the suppression of electron back transfer from SnO 2 to the redox electrolyte (I 3 − ). [21][22][23][24][25] Hence, surface modification of the photoanodes would be an ideal strategy to improve the η LH and η INJ . 26 In this work, we aim to improve the V oc and short circuit current density (j sc ) of the SnO 2 nanocrystal photoanode based DSSC through Zn doping.…”
mentioning
confidence: 99%